FORMULASI DAN UJI EFEKTIVITAS ANTIBAKTERI SEDIAAN HANDWASH SERBUK EKSTRAK DAUN BIDARA TERHADAP BAKTERI Staphylococcus aureus - Syaifullah Saputro; Mifta Khaerati Ikhsan; Tamzil Azizi Musdar; Asti Vebriyanti Asjur (Fakultas Farmasi UMI, 2023)
Bidara leaf is a plant that has the potential to act as an antiseptic. The bidara plant contains various compounds such as flavonoids, alkaloids, triterpenoids, saponins, lipids, and proteins. When kneaded, bidara leaves can produce foam and emit a highly fragrant aroma. The objective of this study was to determine the antibacterial activity of bidara leaf in the formulation of powdered hand wash soap and to identify the effective concentration of bidara leaf extract against Staphylococcus aureus bacteria. The results of the study showed that the hand wash soap preparation containing bidara leaf ethanol extract powder exhibited antibacterial activity against Staphylococcus aureus, with a very strong inhibition zone. Among the formulations, the concentration of 5% in formulation 3 demonstrated the highest inhibitory power of 21.8 mm, classified as a very strong inhibitory power